Anesthetic Agents and Mitochondrial Function A Comprehensive Review of Cellular Bioenergetics and Clinical Implications - Ratri Dwi Indriani; Muhammad Ainur Rosyid Ridho (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2026)
General anesthetic agents have traditionally been understood to function by modulating synaptic receptors. However, emerging evidence highlights mitochondria as a critical, non-canonical target. A comprehensive synthesis of these interactions and their clinical implications is essential for advancing perioperative safety. This narrative review aims to provide a comprehensive analysis of the molecular interactions between common anesthetic agents and mitochondrial function, bridging the mechanisms of cellular bioenergetics with relevant clinical outcomes. A literature search was conducted across major databases, including PubMed, Scopus, and Web of Science, to synthesize and interpret findings from in vitro, in vivo, and clinical studies published between January 2000 and August 2025. Our synthesis reveals that anesthetics directly modulate the electron transport chain, leading to a dual-edged production of reactive oxygen species (ROS) that can be either protective (preconditioning) or damaging (oxidative stress). We find that agents exhibit distinct mitochondrial profiles: sevoflurane often confers protection, propofol shows dose-dependent toxicity linked to bioenergetic failure, and dexmedetomidine acts as a mito-protective adjunct. These interactions disrupt mitochondrial dynamics and can culminate in a